A Tale of Three Spectrums: Deviating from Normative Treatments of Sex and Gender. Issue 7 (2nd July 2020) - Sumerau, J. E.
ABSTRACT: This article presents pathways for deviating from sex and gender analyses norms to better incorporate sex and gender diversity in deviance studies. Synthesizing insights from emerging intersex, transgender, and gender-nonconforming scholarship and prior theorizing on the social construction of gender norms, I outline three separate, yet interrelated spectrums embedded in existing theorizing, and illustrate how more explicit engagement with each of these spectra individually and collectively may speak to unanswered questions and concerns about gender in society. In conclusion, I argue explicit attention to sex and gender spectrums creates possibilities for moving past binary norms in pursuit of better understanding the complexity of sex and gender in the social world.